The Correlation Between Social Support And Self-Esteem Among Final-Year Students At Bhakti Husada University Indonesia - Pranatha, Aria; Apriyanty, Vevi (SAFE-Network, 2025)
The World Health Organization (WHO) reports that low self-esteem is a prevalent mental health issue worldwide, affecting an estimated 121 million people, including 5.8% of men and 9.5% of women, with many cases occurring among individuals in their productive years—university students included. The objective of this study was to determine the relationship between social support and self-esteem among final-year nursing students at Bhakti Husada University Indonesia. This study employed a quantitative approach using a correlational descriptive method and a cross-sectional design. The population consisted of 178 final-year nursing students working on their theses in 2022, from which a sample of 113 was selected through proportionate stratified random sampling. The research instruments included a social support questionnaire and a self-esteem questionnaire, and the data were analyzed using the Spearman’s Rank correlation test. The bivariate analysis yielded a p-value of 0.000 and a correlation coefficient (rho) of 0.547, indicating a significant relationship between social support and self-esteem among final-year students. The findings of this study provide practical implications, particularly for students, educators, and academic institutions, by emphasizing the importance of strengthening social support systems to enhance students’ self-esteem, improve coping abilities, and support their academic completion. It is hoped that students will be able to build greater self-confidence, become more open, and develop supportive relationships with family, friends, and academic advisors while facing the challenges of completing their theses.